A Rhythmic Theory of Attention. Issue 2 (February 2019) - Fiebelkorn, Ian C.; Kastner, Sabine
Abstract : Recent evidence has demonstrated that environmental sampling is a fundamentally rhythmic process. Both perceptual sensitivity during covert spatial attention and the probability of overt exploratory movements are tethered to theta-band activity (3–8 Hz) in the attention network. The fronto-parietal part of this network is positioned at the nexus of sensory and motor functions, directing two tightly coupled processes related to environmental exploration: preferential routing of sensory input and saccadic eye movements. We propose that intrinsic theta rhythms temporally resolve potential functional conflicts by periodically reweighting functional connections between higher-order brain regions and either sensory or motor regions. This rhythmic reweighting alternately promotes either sampling at a behaviorally relevant location (i.e., sensory functions) or shifting to another location (i.e., motor functions). Highlights: Spatial attention and saccadic eye movements are typically coupled but can be uncoupled. Spatial attention samples the environment in theta-rhythmic cycles, leading to alternating periods of either enhanced or diminished perceptual sensitivity. The likelihood of saccades similarly fluctuates at a theta rhythm. Rhythmic attentional sampling is linked to theta-band activity in the large-scale network that directs both spatial attention and saccades. Theta rhythms organize neural activity into alternating attentional states associated with either sampling at a behaviorally relevant location or shifting to another location. Theta rhythms might resolve temporal conflicts between processes that promote either sampling (sensory function) or shifting (motor function), by periodically altering functional connectivity between higher-order brain regions and sensory or motor regions.